Mit Gott, für Vaterland und Menschheit? : Eine europäische Geschichte des freimaurerischen Internationalismus (1845–1935) - Berger, Joachim 1972- (Vandenhoeck & Ruprecht, 2020)
With God, for Fatherland and Humanity is the first comprehensive study of the internationalism of freemasons. It examines, with a focus on Germany, England, France and Italy, how European masonic umbrella associations worked for or against a worldwide organisation of their "brotherhood"